2020
DOI: 10.7554/elife.54090
|View full text |Cite
|
Sign up to set email alerts
|

Bmal1 integrates mitochondrial metabolism and macrophage activation

Abstract: Metabolic pathways and inflammatory processes are under circadian regulation. Rhythmic immune cell recruitment is known to impact infection outcomes, but whether the circadian clock modulates immunometabolism remains unclear. We find that the molecular clock Bmal1 is induced by inflammatory stimulants, including Ifn-γ/lipopolysaccharide (M1) and tumor-conditioned medium, to maintain mitochondrial metabolism under metabolically stressed conditions in mouse macrophages. Upon M1 stimulation, myeloid-specific Bmal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
83
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(98 citation statements)
references
References 58 publications
5
83
1
Order By: Relevance
“…The role of energy metabolism in osteoclasts is shown in Figure 5 . Osteoclasts during differentiation (developmental process) can be regarded as a subgroup of macrophages, and energy metabolism is closely related to the polarization of macrophages ( 135 , 136 ). Metabolic studies on peritoneal macrophages (RAW264.7) and bone marrow-derived macrophages (BMDM) indicated that lysine promotes the activation of M1 and M2, while tyrosine and phenylalanine have opposite effects ( 137 ).…”
Section: Regulators Of the Differentiation Of Macrophages Into Osteocmentioning
confidence: 99%
“…The role of energy metabolism in osteoclasts is shown in Figure 5 . Osteoclasts during differentiation (developmental process) can be regarded as a subgroup of macrophages, and energy metabolism is closely related to the polarization of macrophages ( 135 , 136 ). Metabolic studies on peritoneal macrophages (RAW264.7) and bone marrow-derived macrophages (BMDM) indicated that lysine promotes the activation of M1 and M2, while tyrosine and phenylalanine have opposite effects ( 137 ).…”
Section: Regulators Of the Differentiation Of Macrophages Into Osteocmentioning
confidence: 99%
“…HIF-1 α has been shown to be stabilized by increased pyruvate levels [ 269 ], such as those that occur following PDC inhibition, or by increased succinate levels [ 270 ]. The circadian transcriptional regulator Bmal1, which can be induced by the hormone melatonin [ 271 ], decreases HIF-1 α stability and levels to increase mitochondrial oxidative metabolism [ 272 ]. In lung AECs, stabilization of HIF1- α was shown to cause ER stress and CHOP-mediated apoptosis [ 273 ].…”
Section: Molecular Mechanisms Through Which R-bhb Restores Redox Bmentioning
confidence: 99%
“…Bmal1, a core gene in the body clock, regulates the liver’s biological rhythms. Importantly, it has been pointed out in the literature that the clock gene Bmal1 has crucial effect on macrophages in a variety of diseases, such as inflammatory and metabolic diseases ( Oishi et al, 2017 ; Alexander et al, 2020 ). Furthermore, inflammatory stimulant LPS can also suppress Bmal1 expression in the innate immune response of macrophages ( Curtis et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%